ANALISIS PRAGMATIK DALAM WACANA KAMPANYE POLITIK PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR JAWA TENGAH PERIODE 2013-2018 - Isriani Hardini (JURNAL PENELITIAN, 2014)
This descriptive study discusses the political campaign discourse from a pragmatic angle. The aspects that were examined include speech acts, implicatures, speech meaning, and an effective political campaign discourse form for the community. Data were in the form of billboards and banners of political campaign election of Central Java Governor and Deputy Governor period 2013-2018. There are three main findings of this study. First, speech acts used are speech acts directly and indirectly. Second, most of the speech does not meet the maxim of quality, quantity, relevance, and implementation. Only partial utterances who have fulfilled the maxim of relevance. Third, the purpose of speech is ordered or choose and insinuate or criticize.